Interfuel Substitution in Steam Electric Power Generation - Atkinson, Scott E.; Halvorsen, Robert (Journal of Political Economy, 1976)
A translog normalized restricted profit function is used to study the characteristics of the production function for electric energy. The results indicate that fuel choice in existing steam electric plants responds to changes in fuel prices. The production function is also tested for separability of fuels from capital and labor, homotheticity, returns to scale, and embodied technical change.